Familiar and social influence on alcohol use of college youth - Luisa F. Lema S; María T. Varela A; Carolina Duarte A; María V. Bonilla G (Universidad de Antioquia, 2011)
Objetive: to estimate the prevalence of alcohol use in youth from a private university in Cali - Colombia, and its relation with familiar and social factors. Methodology: secondary source analysis, from a prevalence study. 548 college youth participated, selected through a randomized stratified sampling. Results: the prevalence of alcohol use in life was 96%, last year was 89% and last month was 67%. Actual alcohol use and age of first use were similar between men and women. Age of first use was lower in youth with family members that get drunk frequently, and actual use of alcohol was higher in those with friends that get drunk frequently. Risky or hazardous alcohol use was higher in youth with family members and friends that get drunk frequently. Discussion: the results from this study show the influence of alcohol use in family members and friends in youth's alcohol drinking; pointing out that this practice is socially legitimated, being common in youth's context, facilitating its appearance and maintenance.